Prinsip Syariah dalam Kontrol Investasi Wakaf Kontemporer - Dzar, Muhammad Abu (Berasan: Journal of Islamic Civil Law, 2023)
The purpose of this study is to find out what are the implementation of contemporary waqf investment models, then solve how Islamic law views the implementation of contemporary waqf investment and review in detail how the principles and signs of shari'ah for control of the implementation of contemporary waqf investment. This research is a descriptive-qualitative research. Data obtained through literature reading, analyzed and critically compromised for further narrative description.Â  The primary object of this study is the text, which in turn what is contained in the text will be reviewed in depth with the methodology of taking Islamic law. This research uses descriptive-qualitative analysis, data and information on matters related to this research are studied, reviewed, classified carefully, with the aim of finding legal provisions and principles of control over research problems. Based on data analysis, this study concludes that contemporary waqf investment law is permissible with various provisions according to the investment pattern applied. The sharia principle for contemporary investment control is that the form of investment must be in accordance with sharia and invested in lines that do not contradict the shari'a, should invest in various lines to reduce the possibility of losses that occur, written and officially written and insured with sharia insurance, investment must not conflict with the requirements of the waqf and not harmful to the benefit of the waqf itself.